Advancing commercialization of digital products from federal laboratories - Board on Science, Technology, and Economic Policy; Policy and Global Affairs; The National Academies of Sciences, Engineering, Medicine (Consensus study report, 2021)
Federal laboratories play a unique role in the U.S. economy. Research and development conducted at these labs has contributed to the advancement or improvement of such key general-purpose technologies as nuclear energy, computers, the Internet, genomics, satellite navigation, the Global Positioning System, artificial intelligence, and virtual reality. Digital output from federal laboratories includes data, metadata, images, software, code, tools, databases, algorithms, and statistical models. Importantly, these digital products are nonrivalrous, meaning that unlike physical products, they can be copied at little or no cost and used by many without limit or additional cost. Advancing Commercialization of Digital Products from Federal Laboratories explores opportunities to add economic value to U.S. industry through enhanced utilization of intellectual property around digital products created at federal laboratories. This report examines the current state of commercialization of digital products developed at the federal labs and, to a limited extent, by extramural awardees, to help identify barriers to commercialization and technology transfer, taking into account differences between government-owned, contractor-operated (GOCO) and government-owned, government-operated (GOGO) federal labs.